2020
DOI: 10.1111/dth.14038
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous manifestations of COVID‐19: A case report and a new finding from Egypt

Abstract: Due to its rapidly spreading nature, coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been announced as a pandemic by the World Health Organization in March 2020. 1 Although it is mainly a respiratory condition, it has other manifestations including anosmia and ageusia. 2 Skin manifestations are among the rare conditions associated with the COVID-19, these may include chilblain-like lesions, vascular lesions, varicella-like eruptions, and rash. 3 He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
(4 reference statements)
0
6
0
2
Order By: Relevance
“… N.A. [ 360 ] Petechial and urticarial lesions F 33 Methylprednisolone, antibiotics, anticoagulation therapy [ 361 ] Purpuric rash and maculopapular eruption F 42 N.A. [ 362 ] Maculopapular lesions F 57 None [ 363 ] Chilblain-like lesions 8 M, 8 F 10 N.A.…”
Section: Resultsmentioning
confidence: 99%
“… N.A. [ 360 ] Petechial and urticarial lesions F 33 Methylprednisolone, antibiotics, anticoagulation therapy [ 361 ] Purpuric rash and maculopapular eruption F 42 N.A. [ 362 ] Maculopapular lesions F 57 None [ 363 ] Chilblain-like lesions 8 M, 8 F 10 N.A.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the report by Farouk and Sadek, 1 no enanthem was noted in any patient with urticarial or maculopapular rashes. 4 Regarding the wart-like lesions reported by Farouk and Sadek in their patient as a presumed new clinical cutaneous signs of COVID-19, the authors conveyed it to reactivation of a dormant human papilloma virus (HPV)infection 1. We agree with that as reactivation of endogenous and dormant viruses by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection could somewhat explain the polymorphic eruption associated with COVID-19 in a single viral host 5.…”
mentioning
confidence: 68%
“…We read with interest the case report by Farouk and Sadek publi-shed recently in Dermatologic Therapy. 1 The authors reported an Egyptian health care professional with coronavirus disease 2019 (COVID-19), presented with a progressive pruritic, polymorphic eruption: erythematous, morbilliform, and urticarial. Later, the patient developed "petechial" enanthem of the oral cavity and wart-like lesions of the lower extremities.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, reports from Middle‐Eastern countries are scarce and limited mainly to case reports despite a higher preponderance rate of infection. Herpes zoster, cutaneous small vessel vasculitis, chilblain‐like lesions, wart‐like lesions, oral vesicles, and pityriasis rosea were among the reported signs 7‐12 . It is unclear whether cutaneous signs reported from these nations were truly few or similarities of the reports and poor documentation played a role in its lower priority for publication.…”
mentioning
confidence: 99%